2017
DOI: 10.1002/ijc.31069
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species (ROS) are a key determinant of cancer's metabolic phenotype

Abstract: Cancer cells exhibit a wide range of metabolic phenotypes, ranging from strict aerobic glycolysis to increased mitochondrial respiration. The cause and utility of this metabolic variation is poorly understood. Given that cancer cells experience heavy selection within their microenvironment, survival requires metabolic adaptation to both extracellular and intracellular conditions. Herein, we suggest that reactive oxygen species (ROS) are a key determinant of cancer's metabolic phenotype. Intracellular ROS level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 122 publications
10
98
0
2
Order By: Relevance
“…Furthermore, gene‐set enrichment analyses (GSEA) using hallmark gene‐sets revealed that the 10 most TLR2‐responsive pathways in high TLR2‐expressing human GC cells included ROS, p53, c‐Myc, JAK‐STAT3 and Kras signaling gene networks (Supporting Information Fig. S2C), which are also implicated in respiration, ROS production and cell metabolism . Collectively, these data suggest that the expression of SOD2 is strongly induced at the transcriptional level upon TLR2 activation in high TLR2‐expressing cancer cells, and is associated with enrichment of multiple metabolic or oxidative stress related genes.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, gene‐set enrichment analyses (GSEA) using hallmark gene‐sets revealed that the 10 most TLR2‐responsive pathways in high TLR2‐expressing human GC cells included ROS, p53, c‐Myc, JAK‐STAT3 and Kras signaling gene networks (Supporting Information Fig. S2C), which are also implicated in respiration, ROS production and cell metabolism . Collectively, these data suggest that the expression of SOD2 is strongly induced at the transcriptional level upon TLR2 activation in high TLR2‐expressing cancer cells, and is associated with enrichment of multiple metabolic or oxidative stress related genes.…”
Section: Resultsmentioning
confidence: 86%
“…S2C), which are also implicated in respiration, ROS production and cell metabolism. [20][21][22] Collectively, these data suggest that the expression of SOD2 is strongly induced at the transcriptional level upon TLR2 activation in high TLR2-expressing cancer cells, and is associated with enrichment of multiple metabolic or oxidative stress related genes.…”
Section: Sod2 Is Strongly Induced Upon Tlr2 Activation In Human Gc Cellsmentioning
confidence: 79%
“…Reactive oxygen species (ROS), such as superoxide anion radicals, hydroxyl radicals, and hydrogen peroxide, are natural by‐products of aerobic metabolism . In cells, mitochondria are the primary source of endogenous intracellular reactive species.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Impaired OxPhos together with compensatory fermentation leads to the accumulation of reactive oxygen species (ROS) (85)(86)(87). ROS are carcinogenic and mutagenic, and are largely responsible for the genomic instability and mutations seen in tumor cells (85,(87)(88)(89)(90)(91)(92)(93). In other words, the mutations seen in tumor cells arise as a consequence of impaired energy metabolism (32,64).…”
Section: Role Of Reactive Oxygen Species (Ros) and Oncogenes In The Omentioning
confidence: 99%